Contribución al conocimiento de la estructura foliar de las especies de magnoliáceas colombianas (1985)
Leaf structures including epidermal features of 12 colombian species ofthe genus Talauma and 9 species of the genus Dugandiodendron were studied.All plants investigated grow in wet forets, 5 of them from sea level to 1300 m, the others at altitudes between 1700 to 2600 m.According with the epidermal characteristics, only with few exceptionsthere are no valuable criteria to separate both genera. Usually, epidermal cells are covered with a smooth cuticle, anticlinal walls are straight, and the stomata, situated only on the lower surface of the leaf, and are of the paracytic type. If hairs are present, they are multicellular and uniseriate. Half of the species show thin-walled areas near anticlinal walls in the outer epidermal wall of the upper leaf surface. Some species differ from the common picture: Cuticular sculptures can be observed on the uppers surface of the leaf of Dugandiodendron colombianum, and D. yarumalense, and on the lower surface of Talaurna espinalii. Talaurna virolinensis and Dugandiodendron yammalense have undulated anticlinal cell walls. Thick-walled papillae occur at the lower surface of the leaves of Dugandiodendron colombianum, and D. urraoense.